PCM thermal insulation in buildings - Ismail, K. A R; Castro, J. N C [UNESP] (My University, 1997)
This paper presents the results of a numerical and experimental study of phase change material (PCM) filled walls and roofs under real operational conditions to achieve passive thermal comfort. The numerical part of the study was based on a one-dimensional model for the phase change problem controlled by pure conduction. Real radiation data was used to determine the external face temperature. The numerical treatment was based upon using finite difference approximations and the ADI scheme. The results obtained were compared with field measurements. The experimental set-up consisted of a small room with movable roof and side wall. The roof was constructed in the traditional way but with the phase change material enclosed. Thermocouples were distributed across the cross section of the roof. Another roof, identical but without the PCM, was also used during comparative tests. The movable wall was also constructed as is done traditionally but with the PCM enclosed. Again, thermocouples were distributed across the wall thickness to enable measurement of the local temperatures. Another wall, identical but without the PCM, was also used during comparative tests. The PCM used in the numerical and experimental tests was composed of a mixture of two commercial grades of glycol in order to obtain the required fusion temperature range. Comparison between the simulation results and the experiments indicated good agreement. Field tests also indicated that the PCM used was adequate and that the concept was effective in maintaining the indoor temperature very close to the established comfort limits. Further economical analysis indicated that the concept could effectively help in reducing the electric energy consumption and improving the energy demand pattern. © 1997 by John Wiley & Sons, Ltd.
Keywords: Passive comfort; PCM wall; Thermal barrier; Thermal roof